Optical trapping of microalgae at 735-1064 nm: photodamage assessment - Pilát, Z; Ježek, J; Šerý, M; Trtílek, M; Nedbal, L; Zemánek, P (Journal of photochemistry and photobiology. B, Biology, 2013)
Living microalgal cells differ from other cells that are used as objects for optical micromanipulation, in that they have strong light absorption in the visible range, and by the fact that their reaction centers are susceptible to photodamage. We trapped cells of the microalga Trachydiscus minutus using optical tweezers with laser wavelengths in the range from 735 nm to 1064 nm. The exposure to high photon flux density caused photodamage that was strongly wavelength dependent. The photochemical activity before and after exposure was assessed using a pulse amplitude modulation (PAM) technique. The photochemical activity was significantly and irreversibly suppressed by a 30s exposure to incident radiation at 735, 785, and 835 nm at a power of 25 mW. Irradiance at 885, 935 and 1064 nm had negligible effect at the same power. At a wavelength 1064 nm, a trapping power up to 218 mW caused no observable photodamage.
Keywords: Cells, Cultured; kultivované buňky; Photolysis; mikrořasy; Microalgae; fotolýza; optická pinzeta; Optical Tweezers